PENGEMBANGAN MOBILE LEARNING BERBASIS ANDROID DENGAN METODE KUMON UNTUK MATERI INTEGRAL TAK TENTU - Eka Nur Aini; Syita Fatih 'Adna; Muhamad Najibufahmi (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
This studied developed Android-based mobile learning with the Kumon method for Indefinite Integral material. This studied aims to produce a product in the form of android-based mobile learning which uses the Kumon method steps and test the level of validity and practicality to be used as a learning medium on indeterminate integral material. The research method used in this research is the Plomp method.The results of this development research was in the form of Android-based mobile learning with the Kumon method for indefinite integral material through validation test with an average presentation of 82% according to 8 validators and a practicality test with an average percentage of 67% according to 33 students SMA N 1 Bojong class XII IPA 1. From the results of this studied it can be concluded that Android-based mobile learning with the Kumon method for indefinite integral material meets the requirements with very valid and practical quality to be used as a learning medium that could be used with android in the learning process class in person or online independently on indefinite integral material.